Clinical factors predicting asymptomatic atrial fibrillation in Middle Eastern patients. (14th October 2021) - Al-Makhamreh, H; Tutanji, L; Abdin, B; Salaymeh, O; Al Karmi, F; Abu Eid, E; Obiedat, A; Zaqqa, M; Hammoudeh, A; Hamam, I; Kadri, N; ,
Abstract: Introduction: Anticoagulation has been shown to be highly effective in stroke prevention in patients who have atrial fibrillation (AF). Many patients with AF do not have symptoms and may not seek medical attention. In this study we evaluated the clinical profiles of asymptomatic AF (AAF) patients and compared them to symptomatic ones to find what factors are associated with absence of symptoms. Methods: We analyzed data of 2000 patients enrolled in the prospective multicenter Jordan AF study from May 2019 to October 2020. Symptoms included palpitations (43%), shortness of breath (34%), fatigue (21%), dizziness (11%), chest pain (2%) or syncope (2%) versus no symptoms (30%, n=591). Findings: The average age of the whole group was 67.7±10.2 years and 47% were males. Clinical factors investigated in relation to absence of symptoms are presented in the attached table Conclusion: AAF is associated with the following clinical features: male gender, age above 59 years, diabetes mellitus (DM), cerebrovascular accident (CVA), and chronic renal failure (CRF), CHA2DS2VASC score of 3 and above and HASBLED score of 3 and above, while first episode and paroxysmal AF (PAF) were more likely to be symptomatic. Individuals with these features should be closely evaluated for AAF by means such as pulse monitoring, smart devices and electrocardiogram. Funding Acknowledgement: Type of funding sources: None.